Implementasi Metode Autentikasi dengan Zero Knowledge Proof menggunakan Protokol Feige-Fiat-Shamir Identification Scheme pada Perangkat Internet of Things - Luthfi Maulana; Ari Kusyanti; Fariz Andri Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Authentication is one of many problems about the security of Internet of Things (IoT) devices. Authentication on IoT devices is urgently needed as development on IoT grows. Because IoT devices are constrained devices, a conventional method for authentication is difficult to use. Furthermore, one of the authentication mechanism used in IoT devices called, JSON Web Token (JWT), still has many problems when used on an insecure connection. Zero Knowledge Proof uses the Feige-Fiat-Shamir Identification Scheme protocol which can be used as a solution for problems regarding authentication difficulties on IoT devices. Results from the research show that the system is able to conduct the authentification process using Feige-Fiat-Shamir Identification Scheme protocol with attack resistance limited to keys having an 20 bit length and 20 rounds, a sniffing attack did not result in the compromisation of any confidential data and a brute force attack did not managed to gain the value of modulus n and private key S. Another finding suggests that the amount of rounds has a significant correlation with memory usage of the device and the amount of rounds has an insignificant correlation with the system's execution time.